2006
DOI: 10.1245/aso.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Complications Associated With Sentinel Lymph Node Biopsy: Results From a Prospective International Cooperative Group Trial

Abstract: This study provides a prospective assessment of the sentinel lymph node biopsy procedure, as performed by a wide range of surgeons, demonstrating a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
325
4
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(358 citation statements)
references
References 55 publications
16
325
4
13
Order By: Relevance
“…The incidence of chronic, potentially disabling complications such as lymphedema and paraesthesia is of greater concern to both patients and surgeons, and their incidence at 6 months post-operatively was also evaluated. Previous studies have reported that lymphoedema of the upper extremity occurs in approximately 5-8% of patients post-SNB [19][20][21] and 10-20% of patients post-ALND [22]. In the current analysis, the risk of upper limb lymphoedema and paraesthesia at 6 months was significantly diminished in those undergoing SNB (4.8 vs. 13.3%, SNB vs. ALND).…”
Section: Discussionmentioning
confidence: 41%
“…The incidence of chronic, potentially disabling complications such as lymphedema and paraesthesia is of greater concern to both patients and surgeons, and their incidence at 6 months post-operatively was also evaluated. Previous studies have reported that lymphoedema of the upper extremity occurs in approximately 5-8% of patients post-SNB [19][20][21] and 10-20% of patients post-ALND [22]. In the current analysis, the risk of upper limb lymphoedema and paraesthesia at 6 months was significantly diminished in those undergoing SNB (4.8 vs. 13.3%, SNB vs. ALND).…”
Section: Discussionmentioning
confidence: 41%
“…The ALMANAC trial 28 reported that the rates of lymphedema and sensory loss for patients who received SLNBs were 5% and 11%, respectively, at 12 months. In the trial by Wilke and colleagues, 29 8.6% of patients had axillary paresthesias, 3.8% had a decreased upper extremity range of motion and 6.9% demonstrated proximal upper extremity lymphedema at 6 months. Other complications related to SLNB at the time of prophylactic mastectomy, such as axillary seroma, 20 blue hives and axillary hematomas, 19 have been reported.…”
Section: Discussionmentioning
confidence: 97%
“…The SN biopsy has therefore reduced the morbidity associated with axillary lymph node dissection (ALND) and has readily evolved into the standardized staging procedure in clinically node negative breast cancer patients (Veronesi et al 1999;Golshan et al 2003;Lyman et al 2005;Ferrari et al 2006). For instance, previous studies demonstrated that morbidity of ALND including lymphedema, arm paresthesia, chronic pain and immobility occurs in 5% to 50% of the patients (Kuehn et al 2000;Petrek et al 2001;Silberman et al 2004;Wilke et al 2006). In addition, SN biopsy is an acceptable procedure alterative to ALND for staging the axillary lymph node status in patients with early stage breast cancer (Lyman et al 2005).…”
Section: Introductionmentioning
confidence: 99%